Thermodynamic modeling and composition design for the formation of Zr–Ti–Cu–Ni–Al high entropy bulk metallic glasses. (October 2015) - Satish Idury, K.S.N.; Murty, B.S.; Bhatt, Jatin
Abstract: This work explores the idea of predicting metallic glass forming composition in a multi component alloy for which an equilibrium phase diagram is yet to be deciphered. Deep eutectic regions in a quaternary alloy (Zr–Ti–Cu–Ni) have been extrapolated to the quinary Zr–Ti–Cu–Ni–Al system for designing a potential bulk glass forming composition. PHSS parameter which is the product of mixing enthalpy, mismatch entropy and configurational entropy of an alloy, has been utilized for thermodynamic modeling. PHSS values are computed through substitution of Al into the each of the fifteen quaternary eutectics that have been reported in the literature in the Zr–Ti–Cu–Ni system. A good correlation of PHSS range between modeled alloys and established glass formers indicates the subtle efficacy of this method for high entropy amorphous alloy design through a rationale thermodynamic approach. Highlights: A methodology for high entropy metallic glass composition design is proposed. Optimal window for glass formation is identified through PHSS parameter. Lower order invariant reactions aid in high entropy glassy alloy design.